Modulation Index Variation Effect on Harmonic Behavior of Fifteen Multilevel Inverter Neutral-Point-Clamped Topology - Rabie Benioub; Laid Kadri; Mohamed Adnane; Kenji Itaka (Institute of Advanced Engineering and Science, 2017)
The Market for photovoltaic cells (PV) has grown fast due to a higher demand on PV applications. However, there are still the transport and connection problems of the PV systems to the grid because of the difference in the current form. To assure the adequate connection between the PV sources and the network, the conversion of direct current (DC) to an alternative current (AC) is required and provided by an electronic device known as the inverter. In this last years, the conventional inverter structure reached its limits in power level and conversion performance. The multilevel inverter (MLI) structure was introduced and widely used in high power and high voltage applications to solve the conventional inverter limitation problem. In this paper, the Neutral-Point-Clamped (NPC) topology of the MLI was simulated to evaluate the effect of modulation index variation of the control technique on the harmonic behavior of the fifteen-level NPC. The simulation results were useful for the optimization of the MLI control technique toward the decrease of the harmonic (THD) effect on the NPC MLI.